Circumventing the law: rabbinic perspectives on loopholes and legal integrity - Stein Hain, Elana (Jewish culture and contexts, 2024)
Cover -- Series Page -- Title Page -- Copyright -- Dedication -- Contents -- Introduction -- Chapter 1. (When) Do Circumventions Disrespect the Law -- Chapter 2. Being Explicit About Legal Values and Integrity -- Chapter 3. Romans as Jurists, Rabbis as Lawyers -- Chapter 4. Ha'aramah and Intention -- Chapter 5. Ha'aramah in the Bavli: Discomfort with Ritualized Intention -- Chapter 6. Ha'aramah and Contemporary Legal Theory -- Epilogue. Ha'aramah and Takkanot -- Appendix. Comparing the Yerushalmi's and the Bavli's Use of Ha'aramah Terminology and Concept -- Notes -- Bibliography -- Index -- Acknowledgments.